Pengaruh Produksi, Luas Lahan, Kurs Dollar Amerika Serikat Dan Iklim Terhadap Ekspor Kacang Mete Indonesia Beserta Daya Saingnya - Dionita, Nimas Febri; Utama, Made Suyana (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 4, No. 5, Mei 2015 (pp. 348 - 607), 2015)
Indonesia is an agricultural country in which to grow a variety of plants that can survive in the climate of Indonesia, one of cashews. Cashew Nuts in Indonesia is still exported as logs not in the form of processed so that the export price is still cheap compared to the price of processed cashew. This study aims to determine whether there was an effect simultaneously or partially between production, land area, the United States dollar exchange rate and climate on cashew nut exports as well as to determine the competitiveness of Indonesian exports of cashew nuts against other countries in the US market. The method used in this research is the analysis of the RCA, multiple linear analysis, the classical assumption test and tests of significance. The results of data analysis showed simultaneous production, the US dollar exchange rate and climate have a significant effect on exports cashews 1996-2013. In partial production and land area has a significant positive effect on exports of cashew nuts 1996-2013. Climatic variables and the US dollar exchange rate has no significant effect on exports of cashew nuts 1996-2013. Production variables in this study most dominant influence dibandingnkan other variables. The results of the analysis of RCA to export cashew nuts to the United States menunjukam that the German state has a level of competitiveness when compared with Indonesia, Brazil, India and France.
Keywords: Export, Production, Land, Exchange, Climate, RCA